Ethnic Agricultural Labour in the Okanagan Valley: 1880s to 1960s - Lanthier, Mario; Wong, Lloyd L. (Royal British Columbia Museum, 2002)
Over the past century agriculture in the Okanagan has relied heavily on low cost ethnic labour. The historical documentation of this ethnic agricultural labour is fragmented occurring primarily in photographs, personal diaries, minutes of organizations, newspaper articles, and in some journal articles and books where there is specific mention of a particular ethnic group. This research compiles some of this documentation and synthesizes it into a single document which provides an overall account of the presence and role of ethnic agricultural labour in the Okanagan Valley. More specifically, this research substantiates and examines the presence of the early British settlers and five ethnic groups. They are the First Nations people (1880s - early 1900s and 1940s to 1960s), Chinese (late 1800s to 1930s), Japanese (1942 - late 1940s), Doukhobor (early 1930s - late 1950s), and Portuguese (1955 - early 1960s). –From authors' introduction. Contents: Introduction – The Early British Settlers: 1860s - 1920s – The Chinese: Early 1900s-1930s – The First Nations People: 1880s-present – The Doukhobors: 1930s-1950s – The Japanese: 1940 – The Portuguese: 1940s – Conclusion – References.